Positive models of suffering and psychiatry - Ahmed Samei Huda (BJPsych Bulletin)
Doctors’ typical reaction to patients’ suffering is to alleviate it when clinically appropriate. This has been described as a negative model of suffering, in contrast to the positive model of suffering. In the positive model, suffering can contain an important message of needed change, indicate a response to a psychosocial predicament or be a route to spiritual enlightenment. This approach is briefly critiqued, and circumstances where patients might prefer this approach are described. Doctors can work alongside professionals using this approach while also trying to alleviate suffering if indicated (such as if a patient wishes less suffering or if risk is involved).